Chicken Immune Responses to Vaccination by the Avian Influenza Subtype H5N1 against Avian Influenza - Ramlah, Ramlah; Murtini, Sri; Soejoedono, Retno Damayanti; Natih, Ketut Karuni Nyanakumari; Ningrum, Siti Gusti (UI Scholars Hub, 2023)
Avian Influenza (AI) is one of the strategic animal diseases still considered a priority for control by the Indonesian government. This study aimed to examine the immune response of chickens to various types of H5N1 subtype AI vaccines in Indonesia and to determine the correlation of factors influencing the post-vaccination AI antibody response. Serum samples were tested using the hemagglutination inhibition (HI) test with the standard AI antigen subtype H5N1 strain A/Chicken/Barru/BBVM/41-13/2013 (Clade 2.1.3) and strain A/Chicken/Semarang/04141225-07/2014 (Clade 2.3.2). Antibody titer was calculated using the Geometric Mean Titer (GMT). The correlation analyses were performed to assess the correlation of antibody titer against each of the following factors: age of chicken at the time of sampling, the interval between sampling time and the previous vaccination, and the number of vaccinations performed. The results showed that the average antibody titer value against the AI antigen subtype H5N1 strain A/Chicken/Barru/BBVM/41-13/2013 (Clade 2.1.3) was highest in samples from the South Sumatra Province, namely, Palembang City, which was 26.42 HIU. The results showed a significant correlation (p-value <0,05) between antibody titer and the interval between sampling time and the previous vaccination, the number of vaccination performed and age of chicken at the time of sampling. Therefore, results showed that the immunity developed from vaccination using the AI vaccine seed subtype H5N1 could induce immunity with a protective value of ≥16.